Reframing Teacher Education Through International Collaboration: Exploring Project-Based Learning in Diverse Contexts - Knoblauch, Christoph (International Journal of Advanced Corporate Learning (iJAC), 2024)
This paper focuses on a multi-method study that investigates students’ attitudes and preferences toward project-based collaboration in diverse international contexts. The courses under scrutiny were developed and taught as part of an international blended learning collaboration in teacher education between Dr. Ambedkar University (AUD) in India and Ludwigsburg University of Education (LUE) in Germany. The primary focus of this paper is to analyze and discuss students’ experiences in international project-based environments, with a particular emphasis on the theme of diversity in teacher education. The discussed study employs a multi-method research design that incorporates qualitative interviews and various written feedback forms to gather data on different aspects of the collaborative processes. The findings of this study have the potential to develop future practices and enhance projectbased learning scenarios within higher education. The insights gained from this research can inform pedagogical approaches, and intercultural exchange, ultimately enriching the internationalization efforts within higher education institutions.